Corporate social responsibility communication in the ICT sector: Digital issues, greenwashing, and materiality - Jordan Famularo (International Journal of Corporate Social Responsibility (JCSR), 2023)
Digitalization brings with it new social and governance issues and heightened responsibility, particularly for corporations. In recent years, society has demanded more transparency from companies about digital technology practices, oversight, and impacts. One sector that sharpens the view on these dynamics is information and communication technology (ICT). This study introduces for the first time an examination of corporate social responsibility (CSR) discourse on digital issues among large ICT firms by using signaling theory to analyze a broad set of media (sustainability, ESG, CSR, integrated, impact, purpose, consolidated management, and annual reports as well as issue briefs and webpages). It clarifies how ICT firms present materiality-a reporting concept associated with fair representation and relevance of information-in their CSR reporting on digital topics. It then discusses implications for greenwashing and makes recommendations for improving disclosure credibility.
Keywords: 650; Communication technology; Corporate social responsibility; Cybersecurity; Digital; ESG; Greenwashing; Information technology; Materiality; Privacy; Sustainability